Analysis of the Autism Spectrum Disorder (ASD) Knowledge of Cuban Teachers in Primary Schools and Preschools - Osvaldo Hernández-González (Education Sciences, 2022)
Teachers’ knowledge of autism spectrum disorder (ASD) plays a key role in the successful inclusion of children with ASD in regular schools. The objective of this study was to analyze Cuban teachers’ knowledge of ASD of at inclusive primary schools and preschools and to compare it with the results obtained in previous studies carried out at an international level. To do this, a cross-sectional study was conducted with Cuban teachers from urban and rural areas throughout the country. The sample was selected using a non-probabilistic technique. In total, 131 primary school and preschool teachers participated. Data were collected by applying the Autism Knowledge Questionnaire (AKQ) that measures ASD knowledge. The results indicated that Cuban teachers had an acceptable knowledge regarding ASD (0.57). Primary education teachers (17.58 ± 4.06) showed a higher level of knowledge than preschool teachers (15.35 ± 2.74). Regarding previous training, teachers who claimed to have received some type of specific ASD training (10.88 ± 3.29) made a greater number of errors than teachers who had not received specific training on ASD (8.91 ± 3.06). At the international level, Cuban teachers were observed to have similar knowledge about ASD when compared to active teachers or pre-service teachers from other countries where similar studies have been carried out. The results suggest that the training of Cuban teachers is not yet optimal to educate students with ASD in primary schools and preschools which are open to diversity.